Magnetic Resonance Spectroscopy Assessment of Brain Metabolite Concentrations in Individuals With Chronic Whiplash-associated Disorder: A Cross-sectional Study. Issue 1 (January 2021) - Farrell, Scott F.; Cowin, Gary J.; Pedler, Ashley; Durbridge, Gail; de Zoete, Rutger M.J.; Sterling, Michele
Abstract : Objectives: Pathophysiologic mechanisms underpinning ongoing pain in whiplash-associated disorder (WAD) are not well understood, however, alterations in brain morphology and function have been observed in this population and in other chronic pain conditions. This study investigated metabolite profiles of brain regions in people with chronic WAD compared with controls. Materials and Methods: Thirty-eight individuals with chronic WAD (mean [SD] age, 39.5 [11.3] years, 23 female individuals) and 16 pain-free controls (38.9 [12.7] years, 11 female individuals) underwent multivoxel brain magnetic resonance spectroscopy. At the anterior cingulate cortex (ACC), primary motor cortex (1MC), and somatosensory cortex (SSC), ratios of metabolite concentrations were calculated for N -acetylaspartate (NAA), creatine (Cr), choline (Cho), myo-inositol (Ins), and glutamate/glutamine (Glx). Chronic WAD group participants completed clinical questionnaires and cold and pressure pain threshold assessment. Data were analyzed with hypothesis testing and Spearman correlations ( P ≥0.05), with Benjamini-Hochberg corrections (5% false discovery rate). Results: No group differences were observed for NAA:Cr, NAA:Cho, Cr:Cho, Glx:NAA, Glx:Cr, Glx:Cho, Ins:NAA, Ins:Cr, Ins:Cho or Ins:Glx for left or right ACC, 1MC, or SSC following correction for multiple comparisons. No significant correlations were observed between metabolite ratios and any clinical variable. Discussion: These results suggest that ongoing pain and disability in this population may not be underpinned by metabolite aberrations in the brain regions examined. Further research is required to progress our understanding of cortical contributions to neurophysiologic mechanisms in chronic WAD. Abstract : Supplemental Digital Content is available in the text.